Resin Composites Reinforced by Nanoscaled Fibers or Tubes for Dental Regeneration. (26th May 2014) - Li, Xiaoming; Liu, Wei; Sun, Lianwen; Aifantis, Katerina E.; Yu, Bo; Fan, Yubo; Feng, Qingling; Cui, Fuzhai; Watari, Fumio
Abstract : It has been stated clearly that nanofillers could make an enhancement on the mechanical performances of dental composites. In order to address current shortage of traditional dental composites, fillers in forms of nanofibers or nanotubes are broadly regarded as ideal candidates to greatly increase mechanical performances of dental composites with low content of fillers. In this review, the efforts using nanofibers and nanotubes to reinforce mechanical performances of dental composites, including polymeric nanofibers, metallic nanofibers or nanotubes, and inorganic nanofibers or nanotubes, as well as their researches related, are demonstrated in sequence. The first purpose of current paper was to confirm the enhancement of nanofibers or nanotubes' reinforcement on the mechanical performances of dental restorative composite. The second purpose was to make a general description about the reinforcement mechanism of nanofibers and nanotubes, especially, the impact of formation of interphase boundary interaction and nanofibers themselves on the advanced mechanical behaviors of the dental composites. By means of the formation of interface interaction and poststretching nanofibers, reinforced effect of dental composites by sorts of nanofibers/nanotubes has been successfully obtained.